PEMBERDAYAAN MASYARAKAT AREA GAMBUT MELALUI PELATIHAN PENGOLAHAN MINYAK ATSIRI BERBAHAN DAUN GALAM - Imran Pashar; Hayatus Sa’adah Ayu Lestari; Muddatstsir Idris (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The Peat Hydrological Area (KHG) in South Kalimantan in 2023 covered approximately 238,465 hectares. In Pandahan Village, Tanah Laut Regency, approximately 50 hectares of land are covered with wild galam plants. Galam plants are native to peatlands that naturally associate with endophytic fungi and have the potential to produce essential oils of high economic value as an Indonesian export commodity. Until now, galam has only been used by some communities for firewood without further processing. This Student Creativity Program (PKM) aims to empower farmer groups to acquire the knowledge, skills, and managerial abilities to process galam leaves into essential oils. Activities are carried out using a participatory method through demonstrations and simulations. The program is implemented in three stages: planning, implementation, and evaluation. The activity took place from July 5–19, 2025, in Pandahan Village with 30 participants. Pre-test results showed that only 10% of participants knew the process of processing galam leaves. Following the training and mentoring, post-test results improved significantly, with 100% of participants able to successfully process galam leaves into essential oil. The program continues through monitoring activities to ensure ongoing skill improvement.